Mobile 3D graphics with OpenGL ES and M3G - Pulli, Kari (Morgan Kaufmann series in computer graphics., 2008)
Graphics and game developers must learn to program for mobility. This book will teach you how. ""This book - written by some of the key technical experts ... provides a comprehensive but practical and easily understood introduction for any software engineer seeking to delight the consumer with rich 3D interactive experiences on their phone. Like the OpenGL ES and M3G standards it covers, this book is destined to become an enduring standard for many years to come.""--Lincoln Wallen, CTO, Electronic Arts, Mobile"This book is an escalator, which takes the field to new levels. T